Performance of ADSL / Farah Yasmin Abdul Rahman - Abdul Rahman, Farah Yasmin (2002)
Digital Subscriber Line (DSL) is a new technology that uses the existing telecommunication networks such as the local loop telephone line to accomplish highspeed delivery of voice, video and multimedia. Asymmetric Digital Subscriber Line (ADSL) is asymmetrical, which means it provides higher bit rates in downstream direction (from the telephone central office to the subscriber's site) than the upstream direction (from the subscriber site to the telephone central office). This thesis presents the performance analysis of ADSL. The factors being investigated are the downstream speed and upstream speed of an ADSL signal in various distances. The obtained data are displayed in graphical form and bar chart using Microsoft Excel program. Microsoft Visual Basic Version 6.0 being used as simulation software to display the graphs and charts. The result that were obtained through the testing and data evaluation showed that there are three factors influencing the speed performance of ADSL, which are the copper quality, wire gauge and distance.